Utilization of biotechnological drugs in rare diseases requiring the use of off-label drugs in children in Turkey - AKICI, AHMET (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2021)
Background/aim: Pediatric patients, especially those with rare diseases, represent a population that has a high tendency towards off label drug use (OLDU) and needs a more careful practice of pharmacotherapy than in adults. We aimed to investigate biotechnological drug use in children with rare diseases requiring OLDU. Materials and methods: This retrospective study examined all single-diagnosed OLDU applications (n = 5792) for 4992 children (<18 year) in Turkey. Applications of rare diseases were selected, and their descriptive characteristics were examined, including demographic features of patients, biotechnological drug utilization status, and disease categories. The off-label statuses of the drugs at the end of 2020 were also examined. Results: In total, 77.7% (n = 4501) of OLDU applications were made for rare diseases. Biotechnological drug use was higher in rare disease applications than in nonrare diseases (37.9% vs. 19.2%, respectively; p < 0.0001). Canakinumab was the top applied biotechnological drug (73.2%). Compared to that in small-molecule drugs, the mean age of patients was higher in biotechnological drug-containing applications (8.1 +/- 5.3 vs. 9.7 +/- 4.9, respectively; p < 0.0001). Biotechnological drug use was higher in nonneoplastic rare diseases (40.3%) than in neoplastic rare diseases (26.4%), (p < 0.0001). At the end of 2020, the approval status of the off-label indications covered in 2016 was significantly higher for rare (24.4%) vs. nonrare (5.2%, p < 0.0001) diseases and for biotechnological (32.3%) vs. small molecule (13.9%, p < 0.0001) drugs. In total, 87.7% of the drugs would have to be still used in the off-label setting at the end of 2020. Conclusion: It was seen that more than three-quarters of the pediatric OLDU applications are for rare diseases, and the need for biotechnological OLDU in this group is almost 2-fold of small-molecule drug use. While further projected findings imply a higher approval tendency for rare diseases and biotechnological drugs, there seems to be more room for improvement for pediatric drug use.
Keywords: Off-label drug use; pediatrics; rare disease; biotechnological drugs; canakinumab